The Influence of Motivation and Job Insecurity on Employee Performance: The Mediating Role of Job Satisfaction - Shandra Bahasoan; Dirwan Dirwan; Ridwan Ridwan (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the effects of motivation and job insecurity on employee performance, with job satisfaction acting as a mediating variable. Research Design and Methodology: A quantitative explanatory survey was conducted among 223 employees of PT Pelindo Terminal Container Makassar using a census sampling technique. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Findings and Discussion: The results show that motivation positively and significantly affects both job satisfaction and employee performance. Job insecurity does not significantly influence job satisfaction but negatively affects employee performance. In addition, job satisfaction has a positive and significant effect on employee performance and mediates the relationships between motivation, job insecurity, and performance. These findings indicate that motivated employees are more satisfied and productive, whereas job insecurity directly undermines performance outcomes. Implications: Organizations should strengthen employee motivation, provide clear career opportunities, and reduce perceptions of job insecurity to enhance job satisfaction and performance. Such initiatives can improve productivity and organizational effectiveness. Originality: This study provides empirical evidence on the simultaneous effects of motivation and job insecurity on employee performance through job satisfaction within the port and logistics industry context.